Pre-weaning performance of Zimbabwean Jersey cattle in the subhumid zone of southern Ethiopia - Larbi, Asamoah; Felekke, G.; Hernnadez, J.C.; Alemu, T. (Informa UK Limited, 1995)
Growth of exotic dairy calves in the tropics and subtropics has been investigated (Kabuga and Agyemang, 1984; Adeneye, 1985). Several non-genetic factors like season and year of birth, sex of calf, age and parity of dam, gestation length and management have been reported to influence preweaning performance (Phipps, 1973; Kiwuwa et al., 1983; Kabuga and Agyemang, 1984; Adeneye, 1985; Srivastava et al., 1986). However, information on pre-weaning performance of pure bred exotic dairy calves in Ethiopia is scarce. In October 1987, 92 in-calf Jersey heifers and two bulls were imported from Zimbabwe and Kenya to Soddo, southern Ethiopia, by the Dairy Development Project. This paper reports on preweaning performance of calves born to these animals, in comparison to reports from other parts of the tropics.